Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan Pada PT Angkasa Pura II (Persero) Sultan Thaha Jambi - Muhammad Emil; Fadil Iskandar (Universitas Batanghari Jambi, 2020)
fistly, this research to analyse how ti conduct organizational culture and employee performance. Second how the effect of organizational culture on employee performance at PT Angkasa Pura II (Persero) Sultan Thaha Jambi. The methodology is descriptive quantitative analysis methods. Data used is secondary data.The population become object in this research is employee performance at PT Angkasa Pura II (Persero) Sultan Thaha Jambi . The method for analysis is analysis simple regression, hypotesis test, correlation so determinant coefficient and t_test. The object of this research is PT Angkasa Pura II (Persero) Sultan Thaha Jambi. PT Angkasa PurA II (Persero) Sultan Thaha Airport in Jambi is subsidiary, which is engganged ini air transport services. The business priorities of the company are safety and comfort. Analysis on the research of respondents on score of organizational culture where indicators promoting organizational missions and motivational of higher while in teh discipline in which indicator score variables work with either is score 258 This can be interpreted as employees working in earnest. Simple regression equation model is Y = 5,295 + 0,713 X + e. Test results of ttest is tcount > ttable, in meaning the organizational culture has effect on performance employee. Conclusion, organizational culture and performance employee in good condition. So that organizational culture has effect significant to performance employee on PT Angkasa Pura II (Persero) Sultan Thaha. Suggestion that head manager of PT Angkasa Pura II (Persero) should directly control his subordinate work directly.